Трофические связи ястреба-тетеревятника (Accipiter gentilis L.) на севере Белоруссии - Ивановский, В.В.; Уманская, А.С. (Вестник зоологии, 1981)
Thorough study of the Accipiter gentilis .L trophic relations in the Byelorussian Poozerie in 1972-1978 made it possible to conclude that general exterminationof this species is inexpedient in view o the problem on Corvidae and Columbidae amount limitation.